Additive manufacturing in military and humanitarian missions: Advantages and challenges in the spare parts supply chain. (1st June 2020) - Boer, Jelmar den; Lambrechts, Wim; Krikke, Harold
Abstract: This study focuses on the impact of Additive Manufacturing on the responsiveness, efficiency and sustainability of the spare parts supply chain of armed forces during military and humanitarian missions. These spare parts are slow movers, high tech and highly specific. As a consequence their demand is notoriously variable and difficult to forecast. At the same time they are mission critical. A systematic literature review, desk research of different cases, as well as semi-structured interviews with internal and external stakeholders within the Royal Netherlands Army demonstrate that Additive Manufacturing can reduce lead times, waste, energy use, spare parts inventories, as well as improve system readiness and sustainability of armed forces, specifically during military and humanitarian missions abroad. However, challenges must be met in particular related to energy use, local collaboration, (out-)sourcing, security and intellectual properties. This paper connects Additive Manufacturing and the growing importance of sustainability with the need for well-prepared operational armed forces and outlines an agenda for future research regarding mission based supply chains. Graphical abstract: Image 1 Highlights: The quantity, complexity and age of military systems offer opportunities for AM. AM reduces lead times and responds to mission based supply chain specificities. AM improves system readiness and sustainability of military/humanitarian missions. Mission based AM poses challenges to sourcing, security and intellectual properties.